On the link between democracy and environment - Thomas Drosdowski (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 2006)
Using a considerable number of theoretical and empirical sources, we analyze the relationship between democracy and environment. First, we compare the situation in democracies and non-democracies. Later we discusses environmental distribution conflicts and the role of ratization influences environmental policies, concentrating on the role of economic inequality. Moreover, we discuss the impact of electoral rules and systems, as well as polluting lobbies. Finally, we consider political alternatives and sum up main conclusions.
Keywords: Q58; Q56; D72; 330; democracy; environmental policy; political economy